Parenthood in the context of time and temporarinesses of human existence - L. I. Mosyenko; E. A.Tsvetukhina (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the existential measurement of child shortage social norm and socio and cultural foundations of this modern phenomenon. Relying on ideas M. Foucault and J. Baudrillard, the authors come to conclusion that becoming of the child shortage social norm in Russian and Western societies is due to fundamental changes in the attitude of modern man to his own mortality. The essence of these changes is the oblivion of the human existence temporariness and the view on time as a resource that requires accumulation and effective investment. The modern parenting practices-include «techniques of the self» which are directed on a cyborgization for human bodies. At the foundations for that changes are the global socio and cultural transformations typical of Eurocentric societies